Contribution à une introduction aux études des systèmes hommes-machine - Michel Olivier (Perspectives Interdisciplinaires sur le Travail et la Santé)
The speed of technical progress and size of the present technological systems require from the ergonomist an effort to go beyond the traditional job analysis, limited in time and space. From this view point it should be interesting to bring in the concept of « man-machine systems » and to use for this purpose the conceptual contributions of the different branches of study that deal with systems: general systems theory, theory of self-organizing systems and systems engineering. After a schematic description of these contributions the author first examines some very general characteristics of a system and tries then to limit the field of research about man-machine systems, especially by making a distinction between the process level and the organisation level of a system.